Elda M. Monetti - Di Franco, María Graciela (Praxis Educativa, 2016)
Elda M. Monetti. La didáctica de las cátedras universitarias. Estilos de enseñanza y planificación de clases. <span style="font-size: 10.0pt; line-height: 115%; font-family: 'Verdana','sans-serif'; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: ES; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Noveduc. Coleccion Universidad, 2015